What constitutes sustainable agriculture for different audiences in Germany? A comparative analysis of large‐scale text data - Bartosz Bartkowski; Marieke Cornelia Baaken; Mansi Nagpal; Jan Sodoge; Mariana Madruga deBrito (People and Nature)
Abstract Agriculture contributes in several ways to achieving sustainability objectives. However, there is no agreement among different societal groups, such as farmers, consumers and scientists, on what constitutes ‘sustainable agriculture’. These differences affect how the impacts of agricultural production on sustainability objectives is perceived, which solutions are considered and implemented. In this paper, we investigate the topics discussed under the heading ‘sustainable agriculture’ in German newspapers and agricultural magazines. To this end, we apply topic modelling to extract topics discussed in these two large‐scale text corpora. We complement these with scientific articles as a contrast case. We run separate topic models for each corpus and use the identified topics to compare the patterns qualitatively. Results reveal heterogeneity in the topics across the three corpora with limited overlaps restricted to topics such as agricultural policy. This supports the assumption that farmers and the broader society in Germany have very different perceptions of sustainable agriculture. A surprising result is the absence of topics related to climate change from the agricultural magazine corpus. These disparities may create challenges for designing and implementing democratically legitimized policies to promote sustainable agriculture. Read the free Plain Language Summary for this article on the Journal blog.